Pemberdayaan Ibu Rumah Tangga Menuju Kemandirian Pangan: Urban Farming Berkelanjutan pada Lahan Pekarangan - Hala, Dian Magfirah; Nurnawaty, Andi Ayu; Ifadhila, Ifadhila (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aimed to improve the knowledge and skills of the Housewives Group in Minasa Baji Village, Maros Regency, in managing home gardens through sustainable urban farming. The program was implemented through counseling and field practice methods, which consisted of three stages: program socialization, training and field practice on vegetable cultivation in home gardens and the production of organic fertilizer from household waste, and program evaluation. The evaluation results were analyzed quantitatively and interpreted using the N-Gain method. The results of this community service activity showed an increase of 54.1% in the partners’ knowledge and skills in utilizing home garden areas for cultivating vegetables to meet family needs. In addition, the activity involved the active participation of housewives in processing communal household waste into organic fertilizer that can be used by the partner group or surrounding residents.